2019
DOI: 10.1111/jgs.15777
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Older Adults' Oral Health and Disparities: 1999 to 2004 and 2011 to 2016

Abstract: OBJECTIVES To examine changes in tooth loss and untreated tooth decay among older low‐income and higher‐income US adults and whether disparities have persisted. DESIGN Sequential cross‐sectional study using nationally representative data. SETTING The 1999 to 2004 and 2011 to 2016 National Health and Nutrition Examination Survey. PARTICIPANTS Noninstitutionalized US adults, aged 65 years and older (N = 3539 for 1999‐2004, and N = 3514 for 2011‐2016). MEASUREMENTS Differences in prevalence of tooth loss (having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 11 publications
1
45
0
4
Order By: Relevance
“…As the study by Griffins and colleagues among noninstitutionalized older adults previously found, edentulousness has also decreased among older people in institutional care in Helsinki. Griffin et al also reported findings among home‐limited or long‐term care residents from 2011 to 2016.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As the study by Griffins and colleagues among noninstitutionalized older adults previously found, edentulousness has also decreased among older people in institutional care in Helsinki. Griffin et al also reported findings among home‐limited or long‐term care residents from 2011 to 2016.…”
Section: Discussionmentioning
confidence: 76%
“…To the Editor: Griffin and colleagues investigated changes in tooth loss and whether disparities have persisted among US adults. In their sequential cross‐sectional study, they found that tooth loss largely decreased in all groups of noninstitutionalized older adults.…”
mentioning
confidence: 99%
“…Between 2008 and 2015, the percentage of adults aged 65+ years with dental insurance increased slightly from 32.6 (standard error = 1.1) to 38.4 (1.2) and the percent with a past year dental visit remained relatively stable, 43.9 (1.2) to 46.7 (1.1) (Manski & Rohde, 2017). In addition, studies examining untreated dental disease, another measure of access, suggest that untreated caries prevalence has remained the same among working-aged (about 40%) (Centers for Disease Control and Prevention, 2019) and older adults (about 28%) (Griffin et al, 2019). The latter study also found that disparities by income had actually increased from 1999-2004 to 2011-2016 (Griffin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults are more likely to have chronic disease, and persons with chronic disease have poorer oral health compared to their healthier counterparts. 5 The two leading causes of tooth loss, dental caries and periodontitis, are preventable with routine receipt of primary and secondary prevention. Primary care providers can play an important role in helping patients maintain their oral health.…”
Section: Discussionmentioning
confidence: 99%